A one‐dimensional Cd‐Eu coordination polymer with open‐chain ether Schiff base ligand and 4, 4′‐bipyridine: Synthesis, structure, luminescence property, and antioxidation activities. Issue 10 (5th July 2021) - Dong, Jianping; Li, Ruixue; Jiang, Yuxuan; Sun, Fugang; Qu, Yao; Wu, Huilu
Abstract: A new Cd‐Eu coordination polymer (CP) with open‐chain ether Schiff base ligand bis(3‐methoxysalicylidene)‐3‐oxapentane‐1, 5‐diamine (H2 L) and 4, 4′‐bipyridine (bipy), with composition [CdEuL(bipy)(NO3 )3 ]n, has been synthesized by interfacial diffusion method and further performed structural characterization. The structure analysis revealed that Cd‐Eu CP is an infinite one‐dimensional zigzag coordination polymer formed by CdEuL secondary units through symmetrical coordination bridging bipy. Luminescence property of the Cd‐Eu CP in solid state was also studied. It has been found that the emission spectra of the Cd‐Eu CP exhibit corresponding Eu(III) ion characteristic emission peaks. Antioxidation activities of the ligand and the Cd‐Eu CP were also studied, showing that the antioxidant activities of the Cd‐Eu CP were better than that of H2 L. All provide an irreplaceable reference for the study of the properties of one‐dimensional chain d–f coordination polymers. Abstract : A new one‐dimensional Cd‐Eu coordination polymer with bis(3‐methoxysalicylidene)‐3‐oxapentane‐1, 5‐diamine and 4, 4′‐bipyridine has been synthesized and characterized. The Cd‐Eu CP is an infinite one‐dimensional zigzag coordination polymer. The luminescence intensity of the CP is enhanced by the introduction of the transition metal ion. The Cd‐Eu CP exhibits excellent antioxidant activities against OH· and O2 − · radicals in vitro.